Kualitas DNA dari bakso yang beredar di pasaran Kabupaten Bojonegoro - Hamzah Nata Siswara; Yuny Erwanto; Edi Suryanto (Universitas Sulawesi Barat, 2021)
Meatballs are one of the most popular processed meat products in Indonesia. As processed food produced by livestock, meatballs are susceptible to alduteration. The DNA-based detection method is the most widely used and the susceptibility depend on the DNA quality. The aim of this research was to investigate the DNA isolation procedure of commercial meatballs. The study was conducted by taking 36 samples of meatballs from meatball stalls in Bojonegoro Regency. Reference meatballs as a positive control were prepared in the laboratory. DNA isolation was carried out on the collected sample meatballs, reference meatballs, and 10 species of fresh meat for comparison. The concentration and purity of DNA were measured using a spectrophotometer and visualization of the isolation results was performed using agarose gel electrophoresis and UV transilluminator. The results of DNA isolation were compared descriptively qualitatively between samples of meatballs on the market, reference meatballs, and fresh meat. The results of DNA isolation showed that the meatball samples from the market were successfully isolated by showing the concentration values ​​and visualization with agarose gel electrophoresis. The results of electrophoresis and the value of the DNA purity index showed that the DNA was not pure.